Front Cover Picture: Dual Gold Catalysis: Synthesis of Fluorene Derivatives from Diynes (Adv. Synth. Catal. 2/2017). Issue 2 (4th January 2017) - Bucher, Janina; Wurm, Thomas; Taschinski, Svenja; Sachs, Eleni; Ascough, David; Rudolph, Matthias; Rominger, Frank; Hashmi, A. Stephen K.
Abstract : The front cover image, provided by Svetlana Tšupova, illustrates the gold‐catalyzed conversion of allyl‐ or benzyl‐substituted diyne systems to fluorene derivatives. In a dual gold‐catalyzed process, symbolized on the cover as the work of the Sun‐god, gold vinylidenes are formed and selectively undergo formal insertion into a C( sp 2 )–H bond of the unsaturated side chain. In some cases, isomerization takes place leading to the aromatic system of the final fluorene products. Details can be found in the communication on pages 225–233 (J. Bucher, T. Wurm, S. Taschinski, E. Sachs, D. Ascough, M. Rudolph, F. Rominger, A. S. K. Hashmi, Adv. Synth. Catal .2017, 359, 225–233; DOI:10.1002/adsc.201600987 ).